SUFISM MEMES: Gus Mus’s Representation in Countering the Narrative of Religious Fundamentalism on Social Media - Sabrina, Laila; Ahmadi, Rizqa (AL-TAHRIR, 2021)
Abstract: In Indonesia, Muslim clerics preach the sermon orally. It is considered an effective method to disseminate Islamic teaching. Today, Muslims adopt the development of information technology to propagate the teaching of Islam. One of them is using memes. Commonly, memes are made by quoting wise words from influential figures. This study focused on Gus Musâ€™s wise words. Gus Mus (Musthafa Bishri) is a famous figure in Indonesia. His socio-religious idea is related to the moderate and traditional Muslim. This research aims to find out why some people use the quote of Gus Mus as an object for a meme. Second, it investigates how the memes represent the idea of Gus Mus. It employed qualitative research. The data was gathered through netnography, which focused on specific social media platforms. The data then were analyzed using a sociological approach. It was found that the massive appearance of disturbing memes causes the emergence of Gus Musâ€™s quote meme, particularly comes from fundamentalist communities. These memes represented the spiritual and humanistic ideas of Gus Mus. It is then called Sufism Memes.Ø§Ù„Ù…Ù„Ø®Øµ: Ù‚Ø§Ù… Ø§Ù„Ø¹Ù„Ù…Ø§Ø¡ Ø¨Ù†Ù‚Ù„ Ø£ÙÙƒØ§Ø±Ù‡Ù… Ù„Ø¹Ø§Ù…Ø© Ø§Ù„Ù†Ø§Ø³ ÙÙŠ Ø³ÙŠØ§Ù‚ Ø§Ù„Ø¥Ø³Ù„Ø§Ù… Ø§Ù„Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠ Ø¹Ø§Ø¯Ø©Ù‹ Ù…Ù† Ø®Ù„Ø§Ù„ Ø§Ù„Ù…ØØ§Ø¶Ø±Ø§Øª Ø§Ù„Ø´ÙÙ‡ÙŠØ©. Ù‡Ø°Ù‡ Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© ØªØ¹ØªØ¨Ø± ÙˆØ³ÙŠÙ„Ø© Ù…Ø¤Ø«Ø±Ø© Ù„Ù†Ø´Ø± Ø§Ù„ØªØ¹Ø§Ù„ÙŠÙ… Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©. ÙˆÙ„Ù…Ø§ ØªØ·ÙˆØ± ØªÙƒÙ†ÙˆÙ„ÙˆØ¬ÙŠØ§ Ø§Ù„Ù…Ø¹Ù„ÙˆÙ…Ø§Øª Ø£Ø«Ø± Ø§Ù„Ù…Ø³Ù„Ù…ÙˆÙ† ÙÙ‰ Ù†Ø´Ø± ØªØ¹Ø§Ù„ÙŠÙ… Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ØŒ Ø£ØØ¯Ù‡Ø§ Ø¹Ù† Ø·Ø±ÙŠÙ‚ Ø§Ø³ØªØ®Ø¯Ø§Ù… Ù…ÙŠÙ…ÙŠ. Ø§Ù„Ù…ÙŠÙ…ÙŠØ§Øª ØªØªØ±ÙƒØ¨ Ù…Ù† Ø§Ù‚ØªØ¨Ø§Ø³ ÙƒÙ„Ù…Ø§Øª ØÙƒÙŠÙ…Ø© Ù…Ù† Ø´Ø®ØµÙŠØ§Øª Ù…Ø¤Ø«Ø±Ø©. ÙÙ‰ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ«ØŒ ØµØ§Ø±Øª ÙƒÙ„Ù…Ø§Øª Ø§Ù„ØÙƒÙŠÙ…Ø© Ù„Ø¯ÙŠ Gus Mus Ø§Ù„ØªÙŠ Ø§Ù‚ØªØ¨Ø³Ù‡Ø§ Ø¨Ø¹Ø¶ Ø§Ù„Ù†Ø§Ø³ Ø¯Ø±Ø§Ø³Ø© Ø£Ø³Ø§Ø³ÙŠØ©. Gus Mus (Ù…ØµØ·ÙÙ‰ Ø¨Ø´Ø±ÙŠ) Ù‡Ùˆ Ø¹Ø§Ù„Ù… Ù…Ø´Ù‡ÙˆØ± ÙÙŠ Ø¥Ù†Ø¯ÙˆÙ†ÙŠØ³ÙŠØ§. ÙÙƒØ±ØªÙ‡ Ø§Ù„Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠØ© ÙˆØ§Ù„Ø¯ÙŠÙ†ÙŠØ© Ø£ÙƒØ«Ø± Ø±Ø³ÙˆØ®Ù‹Ø§ Ø¨ÙŠÙ† Ø§Ù„Ù…Ø³Ù„Ù…ÙŠÙ† Ø§Ù„Ù…ØªÙˆØ³Ø·ÙŠÙ† ÙˆØ§Ù„ØªÙ‚Ù„ÙŠØ¯ÙŠÙŠÙ†. ÙØ§Ù„Ø£Ø³Ø¦Ù„Ø© Ø§Ù„Ø±Ø¦ÙŠØ³ÙŠØ© Ù„Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ù‡ÙŠ Ù„Ù…Ø§Ø°Ø§ Ø§Ù‚ØªØ¨Ø³ Ø¨Ø¹Ø¶ Ø§Ù„Ù†Ø§Ø³ ÙƒÙ„Ù…Ø§Øª Gus Mus Ù„Ù…ÙŠÙ…ÙŠØŒ ÙˆÙƒÙŠÙ ØªÙ…Ø«Ù„ Ø§Ù„Ù…ÙŠÙ…ÙŠ ÙÙƒØ±Ø© Gus MusØŸ ØªÙ… Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ù…Ù† Ø®Ù„Ø§Ù„ Ø´Ø¨ÙƒØ© Ø§Ù„Ø¥Ù†ØªØ±Ù†Øª Ù…Ø¹ Ø§Ù„ØªØ±ÙƒÙŠØ² Ø¹Ù„Ù‰ ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØªÙˆØ§ØµÙ„ Ø§Ù„Ø¥Ø¬ØªÙ…Ø§Ø¹ÙŠ Ù…ØØ¯Ø¯Ø© ÙˆØªØÙ„ÙŠÙ„Ù‡Ø§ Ø¨Ù†Ù‡Ø¬ Ø§Ø¬ØªÙ…Ø§Ø¹ÙŠ. ÙˆÙ…Ù† Ø«Ù…ØŒ Ø£Ø¯Ø¹ÙŠ Ø£Ù† Ø¸Ù‡ÙˆØ± Ù…ÙŠÙ…ÙŠ Gus Mus ÙƒØ³Ø±Ø¯ Ù…Ø¶Ø§Ø¯ Ø¨Ø§Ù„Ø¸Ù‡ÙˆØ± Ø§Ù„Ù…ÙŠÙ…Ø§Øª Ø§Ù„Ù‡Ø§Ø¦Ù„Ø© ÙˆØ§Ù„Ù…Ø²Ø¹Ø¬Ø©ØŒ ÙˆÙ„Ø§ Ø³ÙŠÙ…Ø§ Ù…Ù† Ø§Ù„Ù…Ø¬ØªÙ…Ø¹Ø§Øª Ø§Ù„Ù…ØªØ·Ø±ÙØ©. ØªÙ…Ø«Ù„ Ù‡Ø°Ù‡ Ø§Ù„Ù…ÙŠÙ…ÙŠØ§Øª Ù…Ù† Ø£ØµÙ„ Ø§Ù„Ø£ÙÙƒØ§Ø± Ø§Ù„Ø±ÙˆØÙŠØ© ÙˆØ§Ù„Ø¥Ù†Ø³Ø§Ù†ÙŠØ© Ù„Ø¯ÙŠ Gus Mus. ÙØ£Ø³Ù…ÙŠÙ‡Ø§ Ù…ÙŠÙ…ÙŠ ØµÙˆÙÙŠ.Abstrak: Dalam konteks Islam Indonesia, pandangan tokoh agama biasanya disampaikan kepada khalayak melalui ceramah secara verbal. Metode tersebut dinilai efektif untuk mengajarkan Islam. Pada perkembangan terkini, kemajuan teknologi informasi mempengaruhi sebagian besar muslim dalam penggunaan media baru untuk mengajarkan Islam. Salah satunya melalui meme. Biasanya meme dibuat dengan mengutip kata-kata bijak dari tokoh yang berpengaruh. Pada penelitian ini, kata-kata bijak Gus Mus (Musthafa Bishri) menjadi fokus kajiannya. Gus Mus adalah tokoh populer di Indonesia. Gagasan sosial keagamaannya lebih dekat dengan corak Islam moderat dan Islam tradisional. Pertanyaan utama artikel ini adalah mengapa sebagian orang mengutip kata bijak Gus Mus untuk dijadikan meme dan bagaimana kutipan tersebut merepresentasikan gagasan Gus Mus. Data penelitian dikumpulkan menggunakan metode netnografi dengan terfokus pada beberapa platform sosial media tertentu, dan dianalisis menggunkan pendekatan sosiologi. Penulis berpendapat bahwa kemunculan meme tersebut merupakan kepanikan moral atas maraknya meme yang meresahkan, khususnya dari kelompok fundamentalis. Meme tersebut merepresentasikan gagasan humanis dan spiritual Gus Mus. Penulis menandainya dengan istilah Meme Sufistik.